PENGARUH LOKASI, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN SUDUT KOPPI KOTA BATAM - Dadi Akhmad Perdana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study is to analyze the effect of location, of price, of service quality on customer satisfaction at Sudut Koppi Kota Batam,. The method used for sampling in this study is purposive sampling. The sample used in this study was 50 respondents from the customers of Sudut Koppi Kota Batam. Data collection techniques were carried out using a questionnaire technique. While the analysis of the data using quantitative data analysis, namely Multiple Regression, t-and testf-test. The results of this study obtained multiple linear regression equation Y = (-0.451) + -0.255 + 0.316 + 0.152. While the partial hypothesis test (t test) the location variable (X1) has an effect on customer satisfaction at Sudut Koppi Kota Batam, but has a significant effect on customer satisfaction at Sudut Koppi Kota Batam, this is evidenced by the results of the t value 2,970 > t table 2.011 and Sig 0.005 < 0.05, the price variable (X2) has a significant effect on customer satisfaction at Sudut Koppi Kota Batam, this is proven by the t value of 3,294 > t table 2.011, and Sig 0.002 < 0, 05, the service quality variable (X3) has a significant effect on customer satisfaction at Sudut Koppi Kota Batam, this is proven by the t-count value of 3.442 > t table 2.011, and Sig 0.001 <0.05. The value of R Square is 0.910, which means that the location variable (X1), price (X2) and service quality (X3) can explain the customer satisfaction variable by 91.0%, while 9% is explained by other variables not discussed in this study.